2006
DOI: 10.1203/01.pdr.0000219479.95410.79
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Ketogenic Diet for Carnitine Metabolites by Subcutaneous Microdialysis

Abstract: ABSTRACT:The ketogenic diet (KD) provides ketones from the degradation of free fatty acids for energy metabolism. It is a therapeutic option for pharmacoresistant epilepsies. Carnitine is the carrier molecule that transports fatty acids across the mitochondrial membrane for degradation into ketones. The integrity of this transport system is a prerequisite for an adequate ketogenic response. For monitoring of tissue metabolism with KD, we used the sampling method of s.c. microdialysis (MD), which permits minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Levels of C4OH-carnitine and C2-carnitine have been shown to rise in the context of increased ketone body utilization in human and mouse skeletal muscle, and in human subcutaneous interstitial fluid. 4648 Concentrations of C4OH-carnitine, C2-carnitine, and succinate were increased in hearts of the HF group, but not the CH samples, compared to corresponding controls (Figure 4B), consistent with increased flux through the reaction catalyzed by BDH1.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Levels of C4OH-carnitine and C2-carnitine have been shown to rise in the context of increased ketone body utilization in human and mouse skeletal muscle, and in human subcutaneous interstitial fluid. 4648 Concentrations of C4OH-carnitine, C2-carnitine, and succinate were increased in hearts of the HF group, but not the CH samples, compared to corresponding controls (Figure 4B), consistent with increased flux through the reaction catalyzed by BDH1.…”
Section: Resultsmentioning
confidence: 73%
“…The metabolites were selected based on known derivatives of ketone utilization pathway intermediates (Figure 4A), and published work by others focused on tissues known to oxidize ketones. 4648 It should be noted that this set of metabolites are not unique to ketone utilization pathways, given that other metabolic pathways can generate the intermediates. However, our results demonstrate that this metabolite profile is elevated in both HF samples and normal mice fed a ketogenic diet, providing additional support for our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with progressive fatty acid oxidation, we observed a sustained surge in circulating acyl carnitines of various lengths and degrees of saturation with fasting ( Figure 2D). This surge included short-chained acyl carnitines and end products, such as C4:0(OH), a ketone body that correlates with more commonly measured ketone species, such as β-hydroxybutyrate ( Figure 2E) (13). The increase in fully saturated acyl carnitines was also attenuated relative to unsaturated species of similar length (Supplemental Figure 2), although the effect of double bond content was not as strong as that observed for fatty acids.…”
Section: Resultsmentioning
confidence: 88%
“…1). 3-OHbutyrylcarnitine is increased in ketosis as it correlates with 3-hydroxybutyrate levels (Hack et al, 2006). We found that 3-OHbutyrylcarnitine was elevated in T2D ( p  = 0.0002) (Table 2, Fig.…”
Section: Resultsmentioning
confidence: 99%